Marketing Challenges in a Turbulent Business Environment Proceedings of the 2014 Academy of Marketing Science (AMS) World Marketing Congress - Groza, Mark D.; Ragland, Charles B. (Developments in Marketing Science: Proceedings of the Academy of Marketing Science, 2016)
Edited in collaboration with the Academy of Marketing Science, this book contains the full proceedings of the 2014 Academy of Marketing Science World Marketing Congress held in Lima, Peru. The key challenge for marketers during the last two decades has been assuring high satisfaction and strong customer loyalty. Today, consumers' ever-changing desires, instantaneous communication through social media and mobile technology and an unstable global economic climate all come together to stir up market turbulence. This volume explores how traditional and modern marketing practices facilitate development of new and innovative products, help create increased product/service differentiation, ensure better service quality, and most of all, create value for stakeholders even in such a turbulent business environment. Showcasing cross-cultural research from academics, scholars and practitioners from around the world, this volume provides insight and strategies for various marketing issues in today's emerging markets. Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy's flagship journals, Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science. .